(untitled) (Modern education and development, 2025)
Currently, one of the pressing issues in railway transport is the problem of soil movement in windy areas, especially in desert areas. It is important to study the negative effects of wind on railway infrastructure and provide scientifically based solutions in this area. For this purpose, the effects of wind on the stability of rolling stock were studied.